Pengaruh Kelelahan Kerja, Stress Kerja, Motivasi Kerja dan Beban Kerja Terhadap Kinerja Perawat Di RSUD Kota Makassar - Fatimah Fauzi Basalamah; Reza Aril Ahri; Arman Arman (An Idea Health Journal, 2021)
Background: It is undeniable that the nursing profession is a profession that has a high workload and great responsibility. This certainly can affect the performance of nurses in carrying out their duties. This study was conducted to analyze the relationship between work fatigue, work stress, work motivation and workload on the performance of nurses in Daya Makassar Hospital. Methods: This type of research uses an analytical observational method with a cross sectional study design. The sampling method using purposive sampling was carried out on Makassar City Hospital nurses who had met the criteria. In measuring work fatigue, work stress, work motivation, and workload, it is measured using a questionnaire. Results: There are 100 respondents involved in this study. Most of the respondents are in the 31-40 year age group (70%), female (69%), have a bachelor's degree in nursing (59%), and work years > 10 years (73%). The results of statistical tests showed that there was an effect of work stress (p = 0.013), work motivation (p = 0.000), and workload (p = 0.000) on the performance of nurses in Makassar City Hospital. However, work fatigue (p = 0.122) did not affect the performance of nurses in Makassar City Hospital. Conclusion: Work stress, work motivation, and workload affect the performance of nurses in Makassar City Hospital. The most influential factor on the performance of nurses in Makassar City Hospital is workload.